Application of specialist care quality indicators based on doctor-nurse-patient integration model in improving compliance with early ambulation in children with appendicitis (运用医护患一体化专科质量指标提高阑尾炎患儿术后早期下床活动的依从性) - CHENG Lili (程丽丽); ZHU Dan (朱丹); XIE Li (谢丽); WANG Jinjin (王金金) (中西医结合护理)
Objective　Methods Totally 96 children with appendicitis requiring surgical treatment were divided into the two group according to the sequence of hospital admissions: 48 cases with admission date between Jan and Dec, 2020 were included as the control group, receiving routine management after surgery; 48 cases with admission date between Jan and Dec, 2021 were included as the observation group, receiving nursing management using specialist care quality indicators based on doctor-nurse-patient integration model. The primary outcomes included: ambulation distance within 24 hrs after surgery and rate of qualified early ambulation; Time of first exhaust and defecation, postoperative first out-of-bed activity time, first time to food-taking and incidence of symptoms of postoperative discomfort; satisfaction of children’s parents with communication and information support, respect, emotional support and high-quality nursing care. Results ambulation distance within 24 hrs after surgery in the observation group was longer than that in the control group (P＜0. 01). The rate of qualified early ambulation in the observation group (27. 08%) was higher than that in the control group (97. 92% vs. 27. 08%, P＜0. 01). The time of first exhaust and defecation, postoperative first out-of-bed activity time, first time to food-taking in the observation group was shorter than that in the control group(P＜0. 01, respectively). Parents of children in the observation group were more satisfied with communication and information support, respect, emotional support and high-quality nursing care compared with those in the control group(P＜0. 01). Conclusion Application of specialist care quality indicators based on doctor-nurse-patient integration model is potentially effective to improve the children’s compliance with early ambulation, promote the development of standard nursing procedure, improve the parents’ satisfaction and quality of specialist care. The To investigate the effect of specialist care quality indicators based on doctor-nurse-patient integration model in improving compliance with early ambulation in children with appendicitis. (目的 在加速康复外科理念下, 探讨医护患一体化专科护理质量指标管理提高阑尾炎患儿术后早期下床活动中的效果。方法 选取医院小儿外科2020年1月—2021年12月收治的96例阑尾炎的患儿为研究对象。将2020年1月—12月收治的48例患儿作为对照组, 运用常规护理管理落实术后早期下床活动; 将2021年1月—12月收治的48例患儿作为观察组, 运用医护患一体化专科护理质量指标管理落实术后早期下床活动。比较两组患儿术后24 h下床活动距离及达标情况; 术后首次排气排便时间、首次下床活动时间、首次进食时间、术后不适症状(恶心呕吐及腹胀)发生率; 患儿家属在沟通和信息支持、尊重支持、情感支持以及优质护理照护支持四个维度方面的满意度。结果 观察组患儿术后24 h下床活动距离较对照组增加, 差异有统计学意义(P＜0. 01)。观察组术后24 h下床活动达标率(97. 92%)高于对照组(27. 08%), 差异有统计学意义(P＜0. 01)。观察组术后首次下床活动时间、首次排气时间、首次排便时间、首次进食时间均早于对照组, 差异有统计学意义(P＜0. 01), 观察组术后恶心呕吐腹胀发生率低于对照组, 差异有统计学意义(P＜0. 05)。观察组患儿家属在沟通和信息支持、尊重支持、情感支持以及优质护理照护支持四个维度满意度评分高于对照组, 差异有统计学意义(P＜0. 01)。结论 医护患一体化的专科质量指标的实施, 提高了阑尾炎患儿术后早期下床活动的依从性, 促进了标准护理工作的开展, 提高了患儿家属的满意度, 提升了专科护理服务质量水平。)